2005
DOI: 10.1111/j.1439-0442.2004.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Transition Cow Under a Pasture‐based Milk Production System: Metabolic Profiles

Abstract: This study describes the effect of parity (multiparous versus primiparous) and body condition score (BCS) at calving (<3 or > or =3; scale 1-5) on variations of BCS, body weight (BW) and metabolic profiles in Holstein cows grazing on improved pastures. Forty-two cows were studied (21 multiparous and 21 primiparous) from 2 months before to 3 months after calving. BCS, BW and milk production were measured every 2 weeks. Blood samples were taken every 2 weeks to determine total protein, albumin, urea, non-esterif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
51
3
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 31 publications
18
51
3
5
Order By: Relevance
“…The decrease in albumin, urea and cholesterol concentrations at calving may reflect the decreased intake in the peri partum period, as has been reported earlier (Cavestany et al, 2005;Seifi et al, 2007). Total plasma protein concentrations were greater in MH cows, suggesting the better energy/nitrogen balance.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The decrease in albumin, urea and cholesterol concentrations at calving may reflect the decreased intake in the peri partum period, as has been reported earlier (Cavestany et al, 2005;Seifi et al, 2007). Total plasma protein concentrations were greater in MH cows, suggesting the better energy/nitrogen balance.…”
Section: Discussionsupporting
confidence: 55%
“…Milk production curves did not present a peak in milk yield, which has already been observed in other studies conducted with cows calving in autumn (Meikle et al, 2004;Cavestany et al, 2005). One possible reason for these results could be that cows present the lactation peak in winter, when pasture quality is lower, an aspect that should be taken into account when comparison with well-fed cows is performed.…”
Section: Discussionmentioning
confidence: 52%
“…The present study agrees with the results found by Souza & Junior (2009) that stated a continuous increase as days from calving increased. The crescent serum cholesterol concentration levels can be physiologic during the lactation (Cavestany et al 2005) as a result of mobilization of fatty acids in consequence of glucagon secretion and increase of plasma lipoproteins concentration. Higher serum cholesterol concentration values in the Mg-E group can be a result from the supplementation of essential fatty acids from the diet (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The cause of reductions is considered to be due to decrease in food intake or colostrums production, and as food intake increases BUN concentration raises. Increase in dry matter taken with diet is reported to regulate blood protein and urea levels 19 . There are studies asserting that urea concentration is associated with dietary protein degradability, amount of energy and non-protein nitrogen 20 , and with the number of calving 19 .…”
Section: Discussionmentioning
confidence: 99%